2004
DOI: 10.1063/1.1843523
|View full text |Cite
|
Sign up to set email alerts
|

The iron Kα-line as a tool for an evaluation of black hole parameters

A. F. Zakharov

Abstract: Abstract. Recent X-ray observations of microquasars and Seyfert galaxies reveal broad emission lines in their spectra, which can arise in the innermost parts of accretion disks. Simulations indicate that at low inclination angle the line is measured by a distant observer as characteristic two-peak profile. However, at high inclination angles (> 85 0 ) two additional peaks arise. This phenomenon was discovered by using the Schwarzschild black hole metric to analyze such effect. They assumed that the effect is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In fact, the black hole parameter estimates come from a variety of astrophysical observations [41,42,51,60,61,50]. The black hole spin estimates are commonly given by the optical methods, namely by X-ray line profiles [48,36,26,28,86,87] and X-ray continuum spectra [52,53,66], and by quasiperiodic oscillations, the frequency of which enable, in principle, the most precise spin estimates, because of high precision of the frequency measurements. 2 Therefore, we discuss here in detail the orbital resonance model of QPOs, which seems to be the most promising in explaining the observational data from four microquasars, namely GRO J1655-40, XTE 1550-564, H 1743-322, GRS 1915+105 [80,76,77,75] and in Sgr A * [11,13,76], or some extragalactic sources as NGC 5408 X-1 [70].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the black hole parameter estimates come from a variety of astrophysical observations [41,42,51,60,61,50]. The black hole spin estimates are commonly given by the optical methods, namely by X-ray line profiles [48,36,26,28,86,87] and X-ray continuum spectra [52,53,66], and by quasiperiodic oscillations, the frequency of which enable, in principle, the most precise spin estimates, because of high precision of the frequency measurements. 2 Therefore, we discuss here in detail the orbital resonance model of QPOs, which seems to be the most promising in explaining the observational data from four microquasars, namely GRO J1655-40, XTE 1550-564, H 1743-322, GRS 1915+105 [80,76,77,75] and in Sgr A * [11,13,76], or some extragalactic sources as NGC 5408 X-1 [70].…”
Section: Introductionmentioning
confidence: 99%
“…The spin estimates with a ∼ 1 are implied by the Xray observations of AGN as MCG-6-30-15 [52] or the GBHC GRS 1915+105 [53] and are related to a variety of optical phenomena that deserve attention. Among them the most important seem to be the spectral continuum [51][52][53][54][55][56], spectral line profiles [57][58][59][60][61][62][63][64][65][66][67][68][69][70], and quasiperiodic oscillations explained by the orbital resonant models applied to near-extreme black holes [12,[71][72][73][74][75][76][77]. All such objects seem to be possible candidates for the Kerr superspinars and deserve attention and detailed study of data.…”
Section: Observational Signatures Of Kerr Superspinarsmentioning
confidence: 99%
“…Based on our previous results [32,33], we write our own ray-shooting code to check conclusions about the interpretation of observational data in the framework of the theoretical model. We solved several relevant astrophysical problems with our code [34,35,36,37,38,39,40,41,42,43,44], in particular, we generalize Matt et al's result [26] about the existence of extra peaks in relativistic line shapes for the case of a Kerr black hole if a distant observer is located near the equatorial plane [45] (initially Matt et al [26] established their result for a Schwarzschild black hole case) while in [46] we showed that in principle one could constrain a magnetic field, when the magnetic field is strong enough. One can find more recent reviews on theoretical aspects of relativistic line shapes in [47,48].…”
Section: Centennial History Of Black Holes In Briefmentioning
confidence: 99%